Iran's Code of Citizen Rights and Malik Ashtar Amir al-Mominin's troth; Comparison and Collation - Hassan Boosaliki (اخلاق وحیانی, 2024)
Citizenship ethics is one of the branches of applied ethics. Paying attention to the cultural context in citizenship ethics is more necessary than other branches. Due to the serious presence of religion in the cultural context of contemporary Iran, it is necessary to compare the upstream documents with similar religious cases. In this research, the "code of citizen's rights" published by the 11th government of the Islamic Republic of Iran, has been compared with letter 53 of Nahj al-Balagheh (known as the Malik Ashtar's troth). The method of this research is qualitative content analysis. One of the results is that in terms of structural attribution, Malik Ashtar's troth is more appropriate than the Code of Citizen Rights. The contents of these two documents are aligned in these aspects: religious impartiality in the rights of citizens, attention to positive discrimination, attention to the right to criticize the governors and their accountability, effort to gain people's satisfaction. But they are also inconsistent in some ways, including: simultaneously involving the ethics of justice and the ethics of charity, the right to access the governors.